2019
DOI: 10.1002/qua.26145
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the influence of terminal ligands on magnetic exchange coupling in a series of dimeric copper(II) acetate adducts

Abstract: A combination of experimental (SQUID magnetometry) and quantum‐chemical (BS‐DFT, CASSCF(n,m)/NEVPT2, DDCI3) methods is used to probe the influence of terminal ligands on magnetic exchange coupling in the series of [Cu2(μ2‐OAc)4L2] complexes with O‐donor terminal ligands extended by two novel complexes containing phosphine oxide ligands. The possibilities and limitations of these approaches are discussed. The influence of terminal ligands on magnetic superexchange interaction was quantified by two contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…As suggested by previous studies on the exchange interaction between paramagnetic metal ions [ 61 , 62 , 63 , 64 , 65 , 66 , 96 ], the potentially very accurate singlet-triplet energy gap, and thus the J constant, is obtained with the difference dedicated MRCI (DDCI3) even with the minimal active space. This computational technique, in concert with the def2-TZVP basis set, produces J = 173 cm −1 for the model complex [Cu(SQ)(opd)] + , and this prediction is in line with the values 140, 191 and 161 cm −1 that were experimentally determined for structurally similar [Cu(dtbSQ)(dpya)(ClO 4 )] , [Cu(dtbSQ)(bipy)(BF 4 )] and [Cu(dtbSQ)(dpya)(THF) 2 ] + , respectively [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by previous studies on the exchange interaction between paramagnetic metal ions [ 61 , 62 , 63 , 64 , 65 , 66 , 96 ], the potentially very accurate singlet-triplet energy gap, and thus the J constant, is obtained with the difference dedicated MRCI (DDCI3) even with the minimal active space. This computational technique, in concert with the def2-TZVP basis set, produces J = 173 cm −1 for the model complex [Cu(SQ)(opd)] + , and this prediction is in line with the values 140, 191 and 161 cm −1 that were experimentally determined for structurally similar [Cu(dtbSQ)(dpya)(ClO 4 )] , [Cu(dtbSQ)(bipy)(BF 4 )] and [Cu(dtbSQ)(dpya)(THF) 2 ] + , respectively [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Theoretical studies on the exchange coupling between radical ligands and paramagnetic metal ions were performed [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Introductionmentioning
confidence: 99%